2002
DOI: 10.1097/00005537-200204000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in Larynx

Abstract: Although laryngeal papillomatosis is clinically well defined, the mechanisms and treatment modalities of laryngeal HPV infection need further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 90 publications
3
64
0
11
Order By: Relevance
“…Studies dedicated to HPV infections in LSCCs have reported wide variations in frequency that range from 3 to 85% (2,(4)(5)(6)(7)(8)(9)(10). LSCCs are infected with a spectrum of oncogenic and non-oncogenic HPV types.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies dedicated to HPV infections in LSCCs have reported wide variations in frequency that range from 3 to 85% (2,(4)(5)(6)(7)(8)(9)(10). LSCCs are infected with a spectrum of oncogenic and non-oncogenic HPV types.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being associated with well-established risk factors, such as smoking and alcohol use, the development of laryngeal carcinoma (LSCC) has also been reported to be associated with some human papillomaviruses (HPVs) (2). Nearly 30 years ago, Gissman and colleagues detected the DNA sequences of HPV-6 and -11 in genital and laryngeal papillomas (3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations